Comparison of plasma mitochondrial DNA copy number in asymptomatic and symptomatic COVID-19 patients - Shoraka, Shahrzad; Mohebbi, Seyed Reza; Hosseini, Seyed Masoud; Zali, Mohammad Reza (Frontiers in Microbiology, 2023)
Since the beginning of the COVID-19 pandemic, a wide clinical spectrum, from asymptomatic infection to mild or severe disease and death, have been reported in COVID-19 patients. Studies have suggested several possible factors, which may affect the clinical outcome of COVID-19. A pro-inflammatory state and impaired antiviral response have been suggested as major contributing factors in severe COVID-19. Considering that mitochondria have an important role in regulating the immune responses to pathogens, pro-inflammatory signaling, and cell death, it has received much attention in SARS-CoV-2 infection. Recent studies have demonstrated that high levels of cell-free mitochondrial DNA (cf-mtDNA) are associated with an increased risk of COVID-19 intensive care unit (ICU) admission and mortality. However, there have been few studies on cf-mtDNA in SARS-CoV-2 infection, mainly focusing on critically ill COVID-19 cases.In the present study, we investigated cf-mtDNA copy number in COVID-19 patients and compared between asymptomatic and symptomatic cases, and assessed the clinical values. We also determined the cf-nuclear DNA (cf-nDNA) copy number and mitochondrial transcription factor A (TFAM) mRNA level in the studied groups.Material and methods: Plasma and buffy coat samples were collected from 37 COVID-19 patients and 33 controls. Briefly, after total DNA extraction, plasma cf-mtDNA, and cf-nDNA copy numbers were measured by absolute qPCR using a standard curve method. Furthermore, after total RNA extraction from buffy coat and cDNA synthesis, TFAM mRNA levels were evaluated by qPCR.The results showed that cf-mtDNA levels in asymptomatic COVID-19 patients were statistically significantly higher than in symptomatic cases (P value= 0.01). However, cf-nDNA levels were higher in symptomatic patients than in asymptomatic cases (P value= 0.00). There was no significant difference between TFAM levels in the buffy coat of these two groups (P value >0.05). Also, cf-mtDNA levels showed good diagnostic potential in COVID-19 subgroups.Conclusion: cf-mtDNA is probably important in the outcome of SARS-CoV-2 infection due to its role in inflammation and immune response. It can also be a promising candidate biomarker for the diagnosis of COVID-19 subgroups. Further investigation will help understanding the COVID-19 pathophysiology and effective diagnostic and therapeutic strategies.